The gingerbread pup - Boelts, Maribeth 1964-; Hibbert, Hollie (New York Random House, 2020)
Evalina dreams of having a dog to help with her troublesome sheep, but when she bakes a gingerbread dog he wreaks havoc all over town
English stories
Ages 5-8
Grades 2-3
Keywords: Dogs -- Fiction; Gingerbread -- Fiction; Sheep -- Fiction